Role of tumor-derived exosomes in metastasis, drug resistance and diagnosis of clear cell renal cell carcinoma - Jiang, Tiancheng; Zhu, Zepeng; Zhang, Jiawei; Chen, Ming; Chen, Shuqiu (Frontiers in Oncology, 2022)
Renal cancer is one of the most extensively studied human tumors today, with clear cell renal cell carcinoma accounting for approximately 80% of all cases. Despite recent advances in research on clear cell renal cell carcinoma, advanced distant metastasis of the disease, delay in diagnosis, as well as drug resistance remain major problems. In recent years, as an important mediator of material and information exchange between cells in the tumor microenvironment, exosomes have attracted widespread attention for their role in tumor development. It has been reported that tumor-derived exosomes may act as regulators and have an important effect on the metastasis, drug resistance formation, and providing targets for early diagnosis of clear cell renal cell carcinoma. Therefore, the extensive study of tumour-derived exosomes will provide a meaningful reference for the development of the diagnostic and therapeutic field of clear cell renal cell carcinoma. This article reviews the biological role and research progress of tumor-derived exosomes in different aspects of premetastatic niche formation, tumor angiogenesis, and epithelial-mesenchymal transition during the progression of clear cell renal cell carcinoma. In addition, the role of tumor-derived exosomes in the development of drug resistance in clear cell renal cell carcinoma is also addressed in this review. Furthermore, recent studies have found that cargoes of exosomes in serum and urine, for example, a series of miRNAs, have the potential to be biological markers of clear cell renal cell carcinoma and provide meaningful targets for early diagnosis and monitoring of tumors, which is also covered in this article.